Physical and Sports Enterprise Competitiveness - Liudmyla Shuba; Victoria Shuba (Lesya Ukrainka Volyn National University, 2020)
Despite the external and internal aspects, Ukraine continues to develop and modernize in diverse fields of activity. One of the areas that is gaining momentum in recent years is the activities of physical culture and sports organizations and their competitions with each other. The competitiveness of sports organization is a set of qualitative (non-price) and cost characteristics of physical culture and sports organization that meet the specific needs of sports organizations customers. The Research Aimed to analyze the competitiveness of physical culture and sports organization on the basis of relevant indicators to manage the competitiveness level of sports enterprise. Research Organization. The study was conducted from October 1, 2019 till February 29, 2020 on the basis of physical culture and sports organization - sports club «Sportexpert». The analysis of the services competitiveness was carried out on the example of the sports enterprise - sports club «Sportexpert». The integral coefficient method was chosen to assess the competitiveness. Research Results. Competitiveness assessment of physical culture and sports enterprises is impossible without analysis of the services competitiveness they provide. The main advantage of the step-by-step method of competitiveness is the assessment that it involves direct measurement and evaluation of the studied indicators. Furthermore, this technique allows taking into account the significance of certain parameters with the help of weigh coefficients, which makes it possible to determine the degree of their impact on the final integrated indicator of competitiveness. The general index of service competitiveness of visiting the gym in the sports club «Sportexpert» is 0,77. That is, 77 % of sports club visitors are satisfied with the service provided. Conclusions. The obtained results of calculations demonstrate that analyzed sports club generally has good competitiveness assessment. The integral evaluation determination of competitiveness was based on 10 indicators - characteristics of the sports club activity. The strong and weak points of the «Sportexpert» sports club have been defined. The main indicators that needed to be changed were prestige of the club, cost of services, quality of equipment, professionalism of coaches, and efficiency of training programs.